Frege and Łukasiewicz on logical values - Jastrzębski, Hubert; Chlebowski, Szymon (Hybris, 2014)
Our article regards the connections between the views on semantics of Gottlob Frege and Jan Łukasiewicz. We are especially focused on the problem of logical values and their ontological interpetation. The paper is composed of three parts. In the first section we point out the general tendencies in the reception of Frege’s logical theory in the Lvov-Warsaw Philosophical School. The second section is dedicated to Frege’s semantics, especially his analysis of sense and meaning of propositions. In the third section we reconstruct Łukasiewicz’s propositional semantics from the period when he was inspired by Frege’s semantics. We also critically examine the widespread opinion, according to which the ontological interpretation of logical values proposed by Łukasiewicz is entirely consistent with Frege’s concept.